A comprehensive reservoir segmentation for hydrodynamics and water quality assessment - Camila Bergmann Goulart; João Marcos Carvalho; Julio Werner Yoshioka Bernardo; Bruna Arcie Polli; Cristóvão Fernandes; Stephan Fuchs; Tobias Bleninger (Revista Brasileira de Recursos Hídricos)
ABSTRACT Reservoirs present different and intrinsic characteristics from the point of view of physical, chemical, and biological nature from other environmental systems. They therefore should be characterized differently for a better representation aiming for proper planning and management strategies. This paper analyzes eleven reservoirs and develops a classification and zonation strategy for those systems. First, temporal variation and statistical analysis are performed, followed by a residence time calculation, to assess the reservoir's dynamics. Next, stratification and spatial variation analysis are proposed to verify their necessity. Three of the reservoirs analyzed behave as lentic systems, with a high residence time. In addition, all three have significant tributaries, indicating the potential necessity of considering spatial variation for their classification, later verified in 3D modeling. Even if every reservoir is unique in its dynamics and characteristics, the classification scheme is suitable for different types of reservoirs, since it works like a decision tree, where input loads and hydrodynamics are considered.